Integrated Geophysical Investigation of River Ogun Floodplain, Papalanto, Southwestern Nigeria - Olumayowa Temitope IJALEYE; Michael Adeyinka OLADUNJOYE; Afolabi Treasure ADEFEHINTI (GeoScience Engineering, 2021)
A geophysical investigation that involves the integration of Vertical Electrical Sounding (VES), Electrical Resistivity Imaging (ERI), and Ground Penetrating Radar (GPR) methods was conducted on Papalanto, Ogun River floodplain, a location underlain by sedimentary terrain of Southwestern Nigeria. This research aimed to image the underground lithological units and delineate the shallow geologic structures in order to characterize the area for agricultural suitability throughout the dry season. VES results typically outlined three geologic layers which are topsoil, saturated loamy clay, and alluvium. From 2D inverted resistivity results, three major geologic layers, namely topsoil, saturated loamy clay, and alluvium, were outlined and are in very good agreement with the results attained through VES. The first three layers of 3D inverted resistivity sections display a great amount of variation in the distribution of resistivity at superficial depth, made up of low resistive content. From the GPR survey, three geologic layers were also outlined from the results, namely the topsoil, saturated loamy clay, and alluvium. Consequently, the study location can be said to be semi-competent to competent luxuriant farming land in consideration of the resistivity distribution of the floodplain subsurface. Therefore, VES, ERI, and GPR are very effective geophysical methods for describing and classifying the shallow subsurface in reference to the measured physical properties. Hence, they should be applied in related geophysical investigations for better insight into the geology of the subsurface.